Analisis Manajemen Risiko Rekam Medis dalam Upaya Peningkatan Mutu Pelayanan di Klinik X Surakarta - Amallia, Ade; Wijaya, Chayanita Sekar; Nafi’a, Zidni Ilma (Akademi Perekam dan Informasi Kesehatan Imelda, 2026)
The quality of healthcare services is a crucial element in ensuring patient safety, where the management of digital medical records plays a strategic role in supporting service continuity and clinical decision-making. This study aims to analyze risk management in medical record services at Clinic X, Surakarta, and formulate improvement recommendations to enhance service quality. The research applies a descriptive qualitative approach using the Failure Mode and Effect Analysis (FMEA) method. Data were collected through workflow observations and interviews with medical record officers and Diginic system administrators. Risk assessment involved identifying processes, determining failure modes, evaluating severity, occurrence, and detection levels, and calculating the Risk Priority Number (RPN) to prioritize corrective actions. The findings reveal that the highest RPN values are associated with patient registration without ID cards, Diginic system disruptions, and non-compliance with BPJS registration through the Mobile JKN application. These risks affect patient identification accuracy, service flow, and patient experience. Meanwhile, duplicate and delayed data entries have lower risk priorities but still impact operational efficiency and data accuracy. The study concludes that service quality can be improved through strengthened patient identity verification, the establishment of operational procedures during system failures, staff capacity development, and patient education on Mobile JKN use. Future research is recommended to expand the study scope and integrate FMEA with Root Cause Analysis for more comprehensive risk mitigation strategies.